Wearable Microfluidic Diaphragm Pressure Sensor for Health and Tactile Touch Monitoring. Issue 39 (18th August 2017) - Gao, Yuji; Ota, Hiroki; Schaler, Ethan W.; Chen, Kevin; Zhao, Allan; Gao, Wei; Fahad, Hossain M.; Leng, Yonggang; Zheng, Anzong; Xiong, Furui; Zhang, Chuchu; Tai, Li‐Chia; et al.
Abstract: Flexible pressure sensors have many potential applications in wearable electronics, robotics, health monitoring, and more. In particular, liquid‐metal‐based sensors are especially promising as they can undergo strains of over 200% without failure. However, current liquid‐metal‐based strain sensors are incapable of resolving small pressure changes in the few kPa range, making them unsuitable for applications such as heart‐rate monitoring, which require a much lower pressure detection resolution. In this paper, a microfluidic tactile diaphragm pressure sensor based on embedded Galinstan microchannels (70 µm width × 70 µm height) capable of resolving sub‐50 Pa changes in pressure with sub‐100 Pa detection limits and a response time of 90 ms is demonstrated. An embedded equivalent Wheatstone bridge circuit makes the most of tangential and radial strain fields, leading to high sensitivities of a 0.0835 kPa −1 change in output voltage. The Wheatstone bridge also provides temperature self‐compensation, allowing for operation in the range of 20–50 °C. As examples of potential applications, a polydimethylsiloxane (PDMS) wristband with an embedded microfluidic diaphragm pressure sensor capable of real‐time pulse monitoring and a PDMS glove with multiple embedded sensors to provide comprehensive tactile feedback of a human hand when touching or holding objects are demonstrated. Abstract : A flexible microfluidic diaphragm pressure sensor using liquid‐metal microchannels is presented. The sensor is capable of detecting sub‐100 Pa pressures with sub‐50 Pa resolution. As a proof of concept, both heart‐rate monitoring and tactile pressure mapping of a glove with multiple embedded sensors are demonstrated.